ECONOMIC AND FINANCIAL SITUATION OF HOUSEHOLDS IN POLAND – ANALYSIS AND DIAGNOSIS (Polityki Europejskie, Finanse i Marketing)
Families in Poland run households with significantly lower disposable income compared to families in Western European countries. The level of family consumption in Poland in recent years is approaching the EU average, while the level of financial savings is still five times lower than the average. In Poland for many years the relatively low incomes have been achieved by families with many children. Similar relationships exist in the area of housing and household appliances in durable goods. In recent years, after the global financial crisis in 2008, the global and domestic economy began to improve steadily. At the same time the income situation of families in Poland has also started to improve. In addition, the Family 500 Plus program was launched in April 2016 as a key instrument of social family policy in Poland.